Pinjaman Online dalam Perspektif Pendidikan Islam: Studi pada Pengguna Muslim di Jakarta Selatan - Apriyati Dewi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The rapid development of financial technology has significantly increased the use of online lending services among Indonesian society. While online loans provide easier access to financing, they also raise concerns related to Islamic financial literacy, financial behavior, and users’ mental well-being. This study aims to analyze the use of online lending from the perspective of Islamic education among Muslim users in South Jakarta and to examine the role of Islamic financial literacy in shaping financial behavior and mitigating the negative impacts of online loans. This research employed a qualitative approach using a case study design. Data were collected through semi-structured interviews, observations, and documentation involving ten Muslim informants who had used or were currently using online lending services. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the use of online loans is primarily driven by urgent financial needs, business capital requirements, educational expenses, and family-related needs. Most informants demonstrated a basic understanding of the concept of riba; however, their level of Islamic financial literacy remained limited, affecting the quality of their financial decision-making. The study also found that Islamic education plays a significant role in fostering prudence in debt management and financial behavior. Furthermore, online lending may contribute to psychological distress, including stress and anxiety caused by debt repayment obligations. From the perspective of maqāṣid al-sharī‘ah, this phenomenon is closely related to the protection of religion, intellect, wealth, and human well-being. The study highlights the importance of integrating Islamic education and Islamic financial literacy as preventive strategies for addressing the challenges of digital finance in contemporary society.